Gendered Pathways to Bullying Perpetration via Social Achievement Goals – Mediating Effects of Sense of Belonging and Non-inclusive Group Norms. (2nd April 2020) - Bardach, Lisa; Graf, Daniel; Yanagida, Takuya; Kollmayer, Marlene; Spiel, Christiane; Lüftenegger, Marko
ABSTRACT: This study investigated the gender-specific effects of social achievement goals – i.e., social development goals, social demonstration approach goals, and social demonstration avoid goals – on bullying perpetration in a sample of 788 adolescents (53.3% girls), taking into account the mediating role of sense of belonging and non-inclusive group norms. Two-group structural equation modeling results indicated that social demonstration approach goals positively predicted bullying perpetration for both genders. For girls, higher social development goals and for boys, higher social avoidance goals decreased bullying perpetration. Gender-specific effects of belonging and non-inclusive group norms on bullying perpetration occurred. For boys, non-inclusive group norms mediated the relation between all social achievement goals and bullying perpetration. Implications for future research and (gender-sensitive) bullying interventions are discussed.